Quality of Friendship Relationships to Risk of Bullying Behavior in First-Year Students - Ke Lomi, Marthino Khaba; Benu, Juliana Marlin Yusrianti; Ratu, Feronika (Journal of Health and Behavioral Science, 2025)
Abstract. The risk of bullying behavior is an act of intimidation carried out repeatedly by a stronger party against a weaker party, causing harm to the victim physically or emotionally. This study aims to determine the effect of the quality of friendship relationships on the risk of bullying behavior in the Psychology department, Faculty of Public Health, University of Nusa Cendana. This study used quantitative methods. Samples were taken using a purposive sampling technique. Data was collected using two scales: the Friendship Quality Scale (FQS) and the Adolescent Peer Relations Instrument (APRI). The results showed that the quality of friendship relationships in first-year students has a negative and significant influence on the risk of bullying behavior. Thus, the quality of good friendship relationships acts as a protective factor in creating a safe and bullying-free campus environment. Keywords: friendship relationships, students, bullying behavior